2012
DOI: 10.1088/0741-3335/55/1/015001
|View full text |Cite
|
Sign up to set email alerts
|

Transport in threshold plasmas for a confinement transition in the TJ-II stellarator

Abstract: A description and transport analysis (energy and particles) of neutral beam heated plasmas is shown for two almost identical magnetic configurations except for a ≈1% difference in their rotational transform, ι. Due to the low magnetic shear of TJ-II magnetic fields, such difference takes the low order rational ι = 8/5 to the plasma edge in one of them, while in the other the 8/5 value is near the edge but inside the plasma. A transport transition happens at lower density and plasma energy for the configuration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…It is known that the formation of transport barriers in TJ-II is promoted when low order magnetic resonances are placed in the appropriate plasma region. The stability of such barriers is subject to the MHD stability of the corresponding magnetic resonances [43] and a close relationship has been identified between abrupt changes in transport (in the form of transport pulses or the formation of transport barriers), MHD activity and the location of magnetic resonances. Now, applying a novel causality detection technique (the entropy transfer) to quantify the information transfer between magnetic oscillations and locally measured plasma rotation velocity related to ZFs, it is confirmed that magnetic oscillations associated with rational surfaces play an important and active role in confinement transitions [44].…”
Section: Plasma Flows and Electromagnetic Effectsmentioning
confidence: 99%
“…It is known that the formation of transport barriers in TJ-II is promoted when low order magnetic resonances are placed in the appropriate plasma region. The stability of such barriers is subject to the MHD stability of the corresponding magnetic resonances [43] and a close relationship has been identified between abrupt changes in transport (in the form of transport pulses or the formation of transport barriers), MHD activity and the location of magnetic resonances. Now, applying a novel causality detection technique (the entropy transfer) to quantify the information transfer between magnetic oscillations and locally measured plasma rotation velocity related to ZFs, it is confirmed that magnetic oscillations associated with rational surfaces play an important and active role in confinement transitions [44].…”
Section: Plasma Flows and Electromagnetic Effectsmentioning
confidence: 99%
“…Figure 2 shows power balances for the discharges #19065 and #30047. Discharge #19065 has been discussed in [14]. Discharge #30047 corresponds to a configuration of smaller effective helical ripple for which non-local effects are expected to be smaller.…”
Section: Tj-iimentioning
confidence: 99%
“…A spontaneous H-mode was observed in TJ-II [7]. Two main types of the L-H transitions were found, fast transitions [7][8][9] and the so-called L-I-H transitions [10]. This paper focuses on fast transitions.…”
Section: Introductionmentioning
confidence: 99%